2006
DOI: 10.1021/ja060141m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photovoltaic Properties of Two-Dimensional Conjugated Polythiophenes with Bi(thienylenevinylene) Side Chains

Abstract: Three two-dimensional (2-D) conjugated polythiophenes with bi(thienylenevinylene) side chains (biTV-PTs), P1, P2, and P3, were designed and synthesized for application in polymer solar cells. The absorption spectral, electrochemical, and photovoltaic properties of the biTV-PTs were investigated and compared with those of poly(3-hexylthiophene) (P3HT). The biTV-PTs show a broad absorption band from 350 to 650 nm; especially, the absorption spectrum of P3 displays a broad plateau and much stronger absorbance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
613
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 769 publications
(637 citation statements)
references
References 34 publications
16
613
0
5
Order By: Relevance
“…[1][2][3][4][5][6][7] Several successful strategies for the structural design of conjugated polymers, such as donor-acceptor (D-A) copolymerization, [8][9][10] two-dimensional (2-D) conjugation, [11][12][13] and side-chain engineering, [14][15][16] have been developed to enhance their lightharvesting ability, charge mobility, self-assembling, solubility, and turning their molecular energy levels to meet the requirements of organic electronic devices. 5,[17][18][19][20] Poly(thienylenevinylene)s (PTVs), which is one of polythiophene derivatives (PTs) containing alternating thiophene and vinylene units along the main-chains, have been intensively studied for their photoelectrical property and photovoltaic applications, due to their good charge transport property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Several successful strategies for the structural design of conjugated polymers, such as donor-acceptor (D-A) copolymerization, [8][9][10] two-dimensional (2-D) conjugation, [11][12][13] and side-chain engineering, [14][15][16] have been developed to enhance their lightharvesting ability, charge mobility, self-assembling, solubility, and turning their molecular energy levels to meet the requirements of organic electronic devices. 5,[17][18][19][20] Poly(thienylenevinylene)s (PTVs), which is one of polythiophene derivatives (PTs) containing alternating thiophene and vinylene units along the main-chains, have been intensively studied for their photoelectrical property and photovoltaic applications, due to their good charge transport property.…”
Section: Introductionmentioning
confidence: 99%
“…2,[21][22][23][24][25] In addition, previous literatures also have shown that polythiophene derivatives (PTs) with thienylene-vinylene conjugated side chains possess broader absorption spectra and relatively low-lying HOMO energy levels compared with their linear analogues, since the thienylene-vinylene conjugated side chains could extend the p-electron delocalization of polymer backbone. 2,[26][27][28][29][30] For example, chemically graing conjugated side chains onto polymer backbone through vinylene-linkage, such as thienylene-vinylene 31 and bi(thienylenevinylene), 11 is effective to extend the absorption range and down-shi the HOMO energy level of polythiophene. However, the steric hindrance of bulky branches frequently lowers the coplanarity of thiophene rings on the main chain, leading to weak crystallinity and low p-p* absorption intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to enhance the short-circuit current density in PSCs, molecular designs should be conducive to enhancing the absorption ability of the conjugated polymer. As shown in Figure 1, two-dimensional (2-D) conjugation by vinylene linkage, such as thienylenevinylene [16], bi(thienylene-vinylene) [17], phenothiazine-vinylene [18], triphenylamine-vinylene [19], and terthiophene-vinylene [20], has proven to be a successful strategy to enhance lightharvesting ability, charge mobility and self-assembly, and adjust molecular energy levels to meet the requirements of PSCs [17,20,21]. Moreover, Tan and co-workers reported that a series of 2-D conjugated polymers incorporating different thienylene-vinylene derivatives with BDT building blocks, such as PTG1 [22] and PBDT-TID [23], not only attracted much interest but also demonstrated an effective strategy to extend the absorption range and down-shift the HOMO energy level.…”
Section: Introductionmentioning
confidence: 99%
“…Power conversion efficiency (PCE) which is higher than 9% has been reached recently [2][3][4][5][6][7][8][9][10][11][12][13][14]. Currently, BHJ OSCs are based on two types of donor materials, conjugated polymers and small molecules [15,16].…”
Section: Introductionmentioning
confidence: 99%